Not all informal payments are bad: Instrumental variable investigation of the effect of sand-the-wheels, cultural norm, and grease-the-wheels types of payments on life satisfaction - Nazim Habibov; Alena Auchynnikava (Social Sciences and Humanities Open)
In this study, we investigate the effect of making different types of informal payments in public services on life satisfaction. We theorize that the effect of different informal payments on life satisfaction is not universally negative. Specifically, we hypothesize that the direction of the effect depends on the specific type of motivation for making such payments. As such, we articulate three hypotheses on the effect of specific motivations for making informal payments on life satisfaction. Hypothesis 1 postulates that “sand-the-wheels” payments reduce life satisfaction. Hypothesis 2 posits that “cultural norm” payments improve life satisfaction. Hypothesis 3 proposes that “grease-the-wheels” payments improve life satisfaction. We tested these hypotheses on a large sample of 29 diverse countries in Eastern Europe and the former Soviet Union using the quasi-experimental two-stage IV technique and one-stage classic OLS regression. Hypotheses 1 and 2 are confirmed by both IV and OLS. Conversely, Hypothesis 3 cannot be confirmed by either IV or OLS. We conclude that focusing on informal payments in general, rather than on evaluating specific motivations for making them masks the true outcomes of making such payments. Hence, while designing, implementing, and studying anti-corruption policies, decision-makers and researchers should distinguish between different motivations for making informal payments.